2014
DOI: 10.1016/j.ymgmr.2014.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Differential hexosamine biosynthetic pathway gene expression with type 2 diabetes

Abstract: The hexosamine biosynthetic pathway (HBP) culminates in the attachment of O-linked β-N-acetylglucosamine (O-GlcNAc) onto serine/threonine residues of target proteins. The HBP is regulated by several modulators, i.e. O-linked β-N-acetylglucosaminyl transferase (OGT) and β-N-acetylglucosaminidase (OGA) catalyze the addition and removal of O-GlcNAc moieties, respectively; while flux is controlled by the rate-limiting enzyme glutamine:fructose-6-phosphate amidotransferase (GFPT), transcribed by two genes, GFPT1 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…Phospholipase PLD1 ( Teng et al, 2015 ), involved in intracellular membrane trafficking and maintenance of glucose homeostasis in human skeletal muscle ( Huang et al, 2005 ) was rhythmically expressed in vivo and in vitro. Moreover, oscillatory genes in both datasets included NAMPT , KLF11, and GFPT2 , the latter controlling the flux of glucose into the hexosamine pathway, tightly linked to hyperglycemia and insulin resistance ( Coomer and Essop, 2014 ). The expression of NAMPT , a key regulator of NAD + synthesis and muscle maintenance ( Frederick et al, 2016 ), was previously shown to be regulated by CLOCK and BMAL1 in complex with SIRT1 ( Ramsey et al, 2009 ; Garten et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…Phospholipase PLD1 ( Teng et al, 2015 ), involved in intracellular membrane trafficking and maintenance of glucose homeostasis in human skeletal muscle ( Huang et al, 2005 ) was rhythmically expressed in vivo and in vitro. Moreover, oscillatory genes in both datasets included NAMPT , KLF11, and GFPT2 , the latter controlling the flux of glucose into the hexosamine pathway, tightly linked to hyperglycemia and insulin resistance ( Coomer and Essop, 2014 ). The expression of NAMPT , a key regulator of NAD + synthesis and muscle maintenance ( Frederick et al, 2016 ), was previously shown to be regulated by CLOCK and BMAL1 in complex with SIRT1 ( Ramsey et al, 2009 ; Garten et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…At present, very few clinical studies exist to demonstrate a causal link between HBP activation and high glucose-induced complications in diabetic individuals. Studies from our laboratory recently showed increased HBP activation and O-GlcNAc levels in leukocytes of individuals with diabetes and prediabetes (272) and decreased ␤-N-acetylglucosaminidase gene expression with type 2 diabetes (64). Moreover, other researchers have found that individuals with type 2 diabetes displayed an association of glutamine:fructose-6-phosphate amidotransferase mRNA levels and enzyme activity with postprandial hyperglycemia and oxidative stress (274).…”
Section: H159mentioning
confidence: 92%
“…Oxidative stress was considered as a unifying mechanism of diabetic and its complications [3]. Diabetes can lead to abnormal metabolism of energy, carbohydrates, fat and protein [4,5,6]; high glucose and free fatty acids levels can stimulate oxidative stress, increase the expression of inflammatory factors and lead to insulin resistance [7]. IL-6 and TNF-α, as major inflammatory factors, participate in the development of T2DM; the increasing expression of TNF-α and IL-6 can cause pathological injury and diabetes complications [8,9].…”
Section: Introductionmentioning
confidence: 99%